Operational performance of the SAC-C satellite nickel-hydrogen batteries - Barsellini, Diego Rafael (2005)
Processing and analysis of telemetry data of the Argentine SAC-C satellite Ni-H2 batteries are presented. Diagnostic indicators were established in order to evaluate the performance in-flight of the satellite’s electricity storage system. The state of charge of the batteries was related to the hydrogen pressure. A predictive analysis allowed us to early detect failures in the electricity storage system.